Effect of Prey Refuge in a Three Species Food Chain Model with Beddington-DeAngelis Functional Response - Guin, Lakshmi Narayan; Nandi, Sriparna; Chakravarty, Santabrata (Journal of Environmental Accounting and Management, 2026)
The present theoretical investigation concerns itself with a three-species food chain model of the Beddington-DeAngelis variety paying special attention to prey refuge. The analytical treatment yields different conditions for the existence of ecologically feasible equilibria. The local stability analysis is carried out for these equilibria from analytical point of view while their global performance is numerically simulated for an ecologically meaningful choice of parameters. Special emphasis is put on the dynamics of bifurcation of the system fashioned by prey refuge parameter. The numerical simulations reveal that the present food chain model with constant prey refuge prevails upon limit cycle from the stable scenario to reduce the refuge parameter value. This observation supports one to conclude that the prey refuge parameter plays a significant role in controlling the dynamics of bifurcation of the system under consideration.